116k views
0 votes
If h(x) = -2x – 10, find h(-4).
-2
-18
-3
-16

User PulsePanda
by
5.3k points

2 Answers

2 votes

Answer: -2

Explanation:

so the original equation is

h(x) = -2x – 10,

but now we know that x =(-4).

so if we plug that into wherever there's an X we get

h(-4) = -2 x -4 – 10

so now we can solve, which is pretty easy

-2 x -4= 8

8 + -10 = -2

And voila we have the our answer -2

very easy

User Mitchell Gant
by
5.0k points
4 votes

Answer:

-2

Explanation:

replace x with -4 in the h(x) function

h(x) = -2x-10 ➡ h(-4) = (-2)×(-4)-10 ➡8-10 = -2

User Yuyang He
by
4.6k points